Product generation from acidogenic fermentation of nitrogen-deficient wastes : a thesis presented in fulfillment of the requirements for the degree of Master of Philosophy in Environmental Engineering at Massey University, Turitea Campus, Palmerston North, New Zealand - Bowen, Alexa (Massey University, 2007)
Hydrogen, volatile fatty acid (VFA), and ethanol production were assessed from anaerobic fermentation of nitrogen deficient waste streams in order to determine whether nitrogen fixation would take place without nitrogen supplementation. Continuous stirred tank reactors (CSTR) were run under nitrogen deficient conditions with a synthetic glucose-based wastewater being used as the feed. In this study, stable acidogenic fermentation was achieved with the sole nitrogen source coming from nitrogen fixation. A mixed culture of bacteria, sourced from Feilding wastewater treatment plant (located in the lower North island, NZ), was input into two 1L reactors. The two reactors were initially run under nitrogen-sufficient conditions at pH 5.5, which is considered to be the optimum pH for hydrogen production. The available nitrogen level was systematically reduced in order to investigate the effect of a gradual decrease in available nitrogen (corresponding to an increase in COD to nitrogen ratio (COD:N ratio)) on reactor performance. It was found that total VFA production of acetate, propionate, butyrate and valerate remained similar at all nitrogen levels, though the proportions of each VFA changed slightly; while biomass yield decreased as the COD:N ratio increased. The highest hydrogen output was found to be at the highest nitrogen level, while the hydrogen production decreased with decreasing available nitrogen from a COD:N ratio of 53 to 100 due to methane production and then increased again at a COD:N ratio of 500 and 1000 but not to the same level as was produced initially. In contrast, the carbon dioxide production remained similar at all COD:N ratios. Ethanol production greatly increased as the nitrogen level decreased. As a second stage to this study the reactors were run at different pHs under nitrogen deficient conditions in order to determine the effect of pH on the behavior of nitrogen-fixing wastewater treatment systems. One reactor was run at pH 4.0 while the other was maintained at pH 5.5. VFA, ethanol and gas production were compared. It was found that hydrogen and VFA yields were higher at pH 4.0 than at pH 5.5, while ethanol and biomass yields were very similar at the two pHs. The predominant VFA present differed. Though the biomass yields were similar at the two pHs, it was noted that the rate of biological activity was severely reduced at pH 4.0. Overall it seems that nitrogen fixation is able to take place under nitrogen deficient anaerobic conditions with mixed culture bacteria present. pH seemed to have a large effect on overall reactor productivity. Further study could be performed in order to compare different reactor conditions other than pH, such as HRT under nitrogen deficient conditions. Also, comprehensive microbiological investigation could help to determine which bacterial species are present under which environmental conditions, and whether there is a shift in the biomass population with changes in environmental conditions.
Keywords: Sewage; Purification; Microbiology; Anaerobic bacteria -- Industrial applications